Association of Clean and Healthy Living Behaviour Levels with Mental Health and Nutritional Status in Elementary School Students - Dimas Alfarizi; Suherman Slamet; Wildan Alfia Nugroho (UNIB Press, 2025)
This study aims to determine the relationship between the level of clean and healthy living behavior with mental health and nutritional status in elementary school students. The population in this study were fourth grade students with a sample size of 73 students. This study used quantitative research methods and research design using correlation with a cross sectional approach. The instruments used in this study were the Clean and Healthy Living Behavior questionnaire, a mental health questionnaire using the Strength and Difficulties Questionnaire (SDQ), and measurement of nutritional status using the Body Mass Index (BMI). The data analysis used was normality test, linearity test and chi-square test with an error rate of 5% or 0.05. The results of this study indicate that there is no relationship between the level of clean and healthy living behavior and mental health with a sig value. 0.832 > 0.05 and there is no relationship between the level of clean and healthy living behavior and nutritional status with a sig value. 0,459 > 0,05.